2014
DOI: 10.1371/journal.pone.0102753
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Muscle Fatigue and Central Motor Output during a Simulated Soccer Match

Abstract: PurposeTo examine changes in hamstring muscle fatigue and central motor output during a 90-minute simulated soccer match, and the concomitant changes in hamstring maximal torque and rate of torque development.MethodEight amateur male soccer players performed a 90-minute simulated soccer match, with measures performed at the start of and every 15-minutes during each half. Maximal torque (Nm) and rate of torque development (RTD; Nm.s–1) were calculated from maximal isometric knee flexor contractions performed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
94
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 43 publications
22
94
2
3
Order By: Relevance
“…Fatigue in soccer has been the subject of several reviews (Bangsbo et al 2007;Mohr et al 2005;Nedelec et al 2012) and experimental study (Andersson et al 2008;Oliver et al 2008;Rahnama et al 2006;Robineau et al 2012), however, a limited number of investigations have attempted to quantify the neuromuscular fatigue response, with equivocal results (Girard et al 2015;Marshall et al 2014;Nybo et al 2013;Rampinini et al 2011). Fatigue is classically defined as an exercise-induced reduction in the ability of a muscle or muscle group to generate maximal force (Gandevia 2001), which stems from peripheral and central mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue in soccer has been the subject of several reviews (Bangsbo et al 2007;Mohr et al 2005;Nedelec et al 2012) and experimental study (Andersson et al 2008;Oliver et al 2008;Rahnama et al 2006;Robineau et al 2012), however, a limited number of investigations have attempted to quantify the neuromuscular fatigue response, with equivocal results (Girard et al 2015;Marshall et al 2014;Nybo et al 2013;Rampinini et al 2011). Fatigue is classically defined as an exercise-induced reduction in the ability of a muscle or muscle group to generate maximal force (Gandevia 2001), which stems from peripheral and central mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Both calculations of %VA and CAR rely on the superimposed stimulation occurring during a plateau of the MVC, which is not always the case . Consequently, 2 corrections to the %VA calculation have been employed previously . The first defines the superimposed twitch size as the difference between the force following the twitch to the mean force 100 ms earlier .…”
mentioning
confidence: 99%
“…Most of the markers of player fatigue that have traditionally been examined in previous studies in this environment return to baseline values within 3-4 days after a football match and therefore probably do not explain the increased injury rate observed 5 days after a match [61][62][63][64][65][66][67]. One exception to this, however, is the biomechanical changes that have been observed after a football match or similar activity [125][126][127]. It has not been established how long these changes persist after a match, and future studies measuring biomechanical properties over several days after a match will have the potential to establish whether or not they could play a role in the observed relationship between match congestion and injury rates.…”
Section: Risk For Injury In Relation To Match Congestionmentioning
confidence: 97%
“…However, most previously published studies have shown that signs of muscular fatigue often disappear within 72 hours after a football match, [61][62][63][64][65][66][67] whereas the results of Paper III suggest an increased injury rate up to 5 days after a previous match. Other studies have shown that the biomechanical properties of muscles change as they are fatigued after a football match or similar activity, lowering the production of maximal force and altering the angle of peak torque [125][126][127]. This could potentially increase the risk of injuries as muscles are subjected to different activity levels and activity patterns [128].…”
Section: Short-term Match Congestionmentioning
confidence: 99%